DIGITAL REPUTATION OF THE EXECUTIVE POWER BODIES: DISCURSIVE FACTORS AND COMMUNICATIVE TECHNIQUES OF MANAGEMENT - Elena A. Bazhenova; Mariya A. Shirinkina (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 2. Âzykoznanie)
The paper discusses the communicative techniques of reputation management of the executive power bodies in the Russian media space. Comparing the concepts of digital reputation and digital image, the authors argue that, unlike image which is purposefully implemented in the media environment, reputation reflects the internet users’ real opinion about the activities performed by state institutions. The essential features of digital reputation are accumulative character, unpredictability and inertia. The authors define the discursive factors affecting reputation: ambiguously wide audience of the internet, distribution of target groups on different web sites, the unpredictability of users’ assessments, some citizens’ aggressive speech behaviour, etc. More than 2.5 thousand posts by the Ministry of Science and Higher Education of the Russian Federation published in the VKontakte social network and Telegram messenger were selected as the material for the research. The impact of content on the internet audience was evaluated with the ERpost rate at the Popsters service. The authors argue that effective techniques of digital reputation management are the following: communication on a particular internet platform with regard to its target audience, attractive hashtags, the tone of involvement with the interlocutor, rejection of formal style clichés, and some others. The discursive factors of new formal communication are established, and the techniques of managing governmental bodies’ positive digital reputation are described.